An Adult Case of Beta Thalassemia with Right Ventricular Outflow Tract Tachycardia: A Case Report - AS, Prem; PS, Shahanas; Sreekumar, Praveen; NV, Ramaswamy (Journal of Cardiology and Cardiovascular Medicine, 2024)
Beta thalassemia major is a genetic disorder requiring recurrent blood transfusion leading to iron overload in endocrine glands and major organs like the heart. Iron overload in the heart may lead to many conduction abnormalities. This is a case report of a 20-year-old female who was on recurrent blood transfusion. She was on chelation therapy for iron overload. She developed Right Ventricular Outflow Tract Tachycardia (RVOT) which could not be managed with chemical or electrical cardioversion. Her condition was successfully managed with an Automatic Implantable Cardioverter Defibrillator (AICD) implantation and no ventricular tachycardia was observed even after four years of follow-up.